Research trends in communication and tourism: A systematic review and a bibliometric analysis - Angie Lorena Salgado Moreno; Jorge Alexander Mora Forero; Raquel García Revilla; Olga Martínez Moure (Administrative Sciences, 2024)
The aim of this article is to analyze research trends in communication and tourism through a systematic review and bibliometric analysis of the academic literature in order to identify patterns, areas of interest and possible gaps in knowledge, thus contributing to the understanding and development of these interdisciplinary fields. The methodology includes a bibliometric analysis performed with the R Core Team 2022-Bibliometrix software 4.2.3, in addition to the use of VOSviewer software 1.6.20 and a systematic review of the Scopus and Web of Science databases to analyze the most researched topics, authors, their affiliations, countries, most influential publications, keywords and trends. The results of this research are a valuable contribution to the literature and the scientific community by providing a comprehensive and relevant analysis of the current landscape of communication and tourism research. To conclude, this analysis promotes a deeper understanding of the theoretical and conceptual framework of the studies published to date, which is essential for enriching the academic debate on trends in communication and tourism research.
Keywords: 350; bibliometrics; communication; systematic review; tourism